Pola makan dan kebugaran jasmani atlet pencak silat selama pelatihan daerah Pekan Olahraga Nasional XVII Provinsi Bali tahun 2008 - Putu Ayu Widiastuti; BM Wara Kushartanti; BJ Istiti Kandarina (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background : The fulfillment of nutrient intake is a basic need of athletes. The result of observation to some athletes with varied branches of sport indicates that nutrition and physical exercise will simultaneously bring better output. Presently, attention to the administration of nutrition for athletes is lacking, moreover at local level. Meanwhile, providing good nutrition is as important as maintaining sports achievement.Objective : The study aimed to identify support of eating pattern to physical exercise of Bali self-defence athletes during local training of National Sports Week XVII Province of Bali.Method : This was a descriptive analytical study which used qualitative and quantitave approaches and cross sectional design. Subjects of the study were all of 26 self defence athletes participating in local training at National Sports Week Province of Bali. Data gathered were eating pattern, physical fitness (VO2 max and body fat percent), and physiological condition (hemoglobin level). Support of eating pattern to physical exercise was measured in terms of physical fitness using regression and correlation analysis. Result : Most of nutrient intakes of Bali self-defences athletes were low in carbohydrate but high in fat and protein. Statistical analysis showed that there were correlation and effect of vitamin C and Fe intake to VO2 max. There were correlation and effect of carbohydrate to body fat percent. There was protein affected hemoglobin level. Conclusion : Adequate consumption of nutrients was needed to support athletes in doing physical exercise during training period.